2022
DOI: 10.1039/d2ma00125j
|View full text |Cite
|
Sign up to set email alerts
|

Ratiometric electrochemical detection of tryptophan based on ferrocene and carboxylated-pillar[6]arene hybrid metal–organic layers

Abstract: Metal-organic layers (MOLs), which have an ultrathin structure, are a novel class of two dimensional coordination polymers. In comparison with three dimensional metal-organic frameworks, MOLs have more accessible active sites...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…First reported by Ogoshi in 2010, carboxylated pillar­[ n ]­arenes have received a lot of attention in aqueous supramolecular chemistry . For example, they have been used in various host–guest assemblies, , as sensors, drug delivery systems, , in supramolecular chemotherapy, , for cell imaging, , or as scaffolds for supramolecular polymers . However, their solid-state assemblies and structures have barely been touched in comparison to flourishing solution host–guest chemistry.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…First reported by Ogoshi in 2010, carboxylated pillar­[ n ]­arenes have received a lot of attention in aqueous supramolecular chemistry . For example, they have been used in various host–guest assemblies, , as sensors, drug delivery systems, , in supramolecular chemotherapy, , for cell imaging, , or as scaffolds for supramolecular polymers . However, their solid-state assemblies and structures have barely been touched in comparison to flourishing solution host–guest chemistry.…”
Section: Introductionmentioning
confidence: 99%
“…We decided to fill this gap by directing our attention to the crystallization and structure elucidation of carboxylated pillar[n]arenes and their supramolecular assemblies. We managed for the first time to trap in the crystal state both pillar [5]arene 14 and pillar [6]arene 15 in the form of host−guest complexes. We have shown that carboxylated pillar [5]arene (CPA5) forms inclusion and exclusion complexes with electron-deficient viologen guests 16 and coordination complexes with metal cations.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation